Survivability Rates Based on Molecular Subtype, Stage and Metastasis of 36 months cohort in Breast Cancer Patients - Adi Wijayanto; John S. L. A. Pieter; Prihantono; Salman Ardy Syamsu; Nilam Smaradhania Thaufix; Amirullah Abdi (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: Breast cancer treatment is carried out at the early stage of the disease, and a comprehensive assessment of the subtype, stage, and incidence of metastases is required. This study aims to determine breast cancer patients' overall survival (OS) and disease-free survival (DFS) based on subtype, stage, and incidence of metastases. Methods: An observational analytic study with a retrospective cohort design was performed on eligible breast cancer patients at Wahidin Sudirohusodo Hospital from 2016 to 2019. Univariate analysis, and the Kaplan-Meier survival log-rank method (Mantel-Cox), were used to determine differences in survivability rates (OS and DFS) based on subtype, stage, and incidence of metastases. Results: A total of 172 breast cancer patients from 32 years to 84 years with a mean age of 53.5 years. The most subtypes were Luminal A (34.9%) patients, and the least was Luminal B (15.7%) patients. A total of 85 (49.4%) patients survived during these three years, while 87 (50.6%) died. Based on the results of statistical tests in this study, there were no significant differences between the subtypes with DFS and OS, but on the contrary, there was a significant difference between the stage and incidence of metastases with OS and DFS (p<0.05). Conclusions: There were no statistically significant differences between the subtypes with OS and DFS. This study showed a significant difference between the stage and incidence of metastases with OS and DFS